Morphological and molecular characterization of adults and larvae of Crassicauda spp. (Nematoda: Spirurida) from Mediterranean fin whales Balaenoptera physalus (Linnaeus, 1758). (August 2019) - Marcer, F.; Negrisolo, E.; Franzo, G.; Tessarin, C.; Pietrobelli, M.; Marchiori, E.
Abstract: Crassicauda boopis is known to infect the kidneys and vascular system of mysticetes included Balaenoptera physalus and has been recently reported in Mediterranean waters. Identification at the species level relies on the observation of morphological features of the adult parasites, but field conditions during necropsy and the massive reaction of the host's immune system often prevent optimal conservation of the extremities. Moreover, larval stages of Crassicauda have never been described and no sequences are available in public databases to help such identification. Adult and larvae of Crassicauda were isolated from four specimens of B . physalus and studied with morphological and molecular techniques. Specimens of C . anthonyi, C . grampicola and Crassicauda sp. isolated from Ziphius cavirostris, Grampus griseus, Stenella coeruleoalba and Tursiops truncatus respectively were studied as well. Sequences of nuclear markers 18S and ITS-2 and of mitochondrial gene cox1 were obtained and phylogenetic relationships within the genus Crassicauda were analysed. Analysis of the ITS2 grouped the different species in accordance with morphological identification, as already evidenced in literature for other Spirurida. A higher intra-specific variability was observed for the cox1 gene, for which two species ( C. grampicola and C. anthonyi ) did not appear as monophyletic in the tree. Well-developed non-attached larval specimens in the intestinal lumen of a whale calf were molecularly identified as C . boopis, allowing new insights on the life cycle of this species. This work broadens the genetic database on cetaceans parasites, allowing species identification even in challenging field conditions or in poor conservation of the samples; moreover, the first morphological description of C . boopis larvae is provided. Graphical abstract: Image 1 Highlights: Crassicauda boopis, C. anthonyi, C. grampicola and a Crassicauda sp. are molecularly studied here. First morphological descriptions of larval stages of Crassicauda are provided. Phylogenetic analyses show ITS-2 as the more efficient marker compared to cox1 for identification. New insights on life cycle of Crassicauda boopis are described.